Pengaruh Pelayanan Keamanan dan Jaminan Keselamatan Penerbangan terhadap Kepuasan Penumpang di Bandar Udara Mopah Merauke - Klara, Ferse Liana; Rezty Fauziah Novianty Z (Jurnal Ground Handling, 2025)
Security and safety assurance services are crucial aspects in the aviation world that have a direct impact on passenger satisfaction at airports. This study aims to examine the effect of flight security and safety assurance services on passenger satisfaction at Mopah Merauke Airport. This study uses a quantitative approach by distributing questionnaires to 100 respondents as research samples. The population in this study were passengers at Mopah Merauke Airport. There are three variables in this study, namely security services (X1), safety assurance (X2), and passenger satisfaction (Y). The research instruments were analyzed using validity and reliability tests. Respondent data were processed using the classical assumption test, while the research hypothesis was tested using multiple linear regression analysis, partial test (t test), model feasibility test (F test), and coefficient of determination test (R²). The results of data processing and testing of the three variables showed that security services had a positive effect of 0.142 on passenger satisfaction. The results of the t-test of the Security Service variable (X1) show a t-value of 2.126, which means that the calculated t> t table (2.126> 1.985) with a significance level of 0.036 <0.05. This shows that there is an influence of the Security Service variable (X1) on Passenger Satisfaction (Y). Safety assurance also has a positive influence of 0.599 on passenger satisfaction. The results of the t-test of the Safety Assurance variable (X2) show a t-value of 5.848, which means that the calculated t> t table (5.848> 1.985) with a significance level of 0.000 <0.05. This shows that there is an influence of the Safety Assurance variable (X2) on Passenger Satisfaction (Y). The results of the determination coefficient test show an R value of 0.643 with an R-square calculation result of 0.413. This means that the Security Service (X1) and Safety Assurance (X2) variables are able to influence Passenger Satisfaction (Y) of passengers at Mopah Merauke Airport by 41.3%.